Application software with wordperfect 5.1, TWIN, and dBase III plus - Curtin, Dennis P. (Englewood Cliffs, New Jersey : Prentice-Hall, 1990)
An existing revolution is going on in today's businesses and you are going to play on important role. Not too many years ago, most, information in the office was processed on machines that were primarily mechanical in natures.
Part One. Microcomputer Systems -- Part Two. The Operating System -- Part Three. Word Processing Applications -- Part Four. Spreadsheet Applications -- Part Five. Database Management Applications -- Appendixes.
Includes index.
Keywords: WORDPERFECT (COMPUTER FILE)